Dinamika Interaksi Sosial Antara Siswa Reguler dan Anak Berkebutuhan Khusus dalam Konteks Kelas Inklusi SD Alam Amani Karawang - Pravangasta Oviana Eka Wulandari; Agustinus Setyawan; Alden Nelson (EduInovasi: Journal of Basic Educational Studies, 2025)
This study aims to explore the social dynamics between regular students and students with special needs at Sekolah Dasar Alam Karawang, to analyze the factors influencing social interactions in inclusive classrooms, and to describe the strategies used by teachers to facilitate positive social interactions between both groups. This research employs a qualitative approach using a case study method. Data were collected through observation, in-depth interviews, and documentation. The data analysis was conducted using the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. The findings reveal that the social dynamics between regular students and students with special needs in inclusive classrooms are varied. Regular students generally show curiosity and a willingness to help, while students with special needs—such as those with ADHD, autism, and cerebral palsy—face challenges in communication, emotional regulation, and social behavior. Interaction barriers are also influenced by the lack of understanding among regular students about the concept of inclusion, which often leads to negative attitudes. However, with proper guidance and sustained interaction, empathy and acceptance can be developed. Teachers play a crucial role in creating an inclusive environment through collaborative learning strategies, heterogeneous grouping, and providing education on diversity to all students.